ANALISIS DAMPAK KUALITAS PERSAHABATAN PADA PENINGKATAN KINERJA DAN KEBAHAGIAN DI TEMPAT KERJA GENERASI MILENIAL - Herlina .; Riris Loisa (Metacommunication, 2018)
ABSTRACT                 Humans need social relationships with others. Social relationships can make human life more colorful. Close social relationships are often called friends. Friendship can make life happier. A quality friendship relationship in the workplace can improve performance but less quality friendships will hinder employee performance. The happiness of the workplace is derived from the conditions of the working environment, the communication climate in the workplace and the fulfillment of the appropriate rights of the rich. Climate of communication gained from friendship among colleagues. Having a workplace friend can reduce work pressure. Friendship is a motivational drug and a place to share information. This research is a descriptive quantitative research and association by using regression analysis sedehana. The sample of this study is 60 millenial generations that have been employed being taken identical. The results showed that Friendship Quality and Improving Performance have a positive relationship, Friendship Quality and Happiness have positive relationship, Improving Performance and Happiness have positive relationship, Friendship Quality has an effect on Improving Performance, Friendship Quality has an effect on Happiness. Millennial generation's picture is the average Friendship Quality in the workplace of 58.72%, the average contribution of the Improving Performance of 66.25%, the average of friendship contribution in forming a happy Happiness feeling of 63.5%.Keywords:  Friendship Quality, Improving Performance, Happiness.